2019
DOI: 10.1371/journal.pone.0220701
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceuticals imports in Tanzania: Overview of private sector market size, share, growth and projected trends to 2021

Abstract: Background To assess the extent to which foreign pharmaceutical imports vary from year to year and identifying leading generic and branded formulations, key countries and key importers of pharmaceuticals in private sector supply chain. Methodology A systematic analysis of data for pharmaceutical imports from the Ministry of Health.Data from 2013 to 2016 fiscal years and relevant documents were accessed from the Tanzania Food and Drugs Authority (TFDA). Data cleaning was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…We found a higher dominance of suppliers of antibiotics from India. In the top ten suppliers of antibiotics in Tanzania, this trend has also been shown in other studies [37], indicating a good trade between Tanzania and India in the sales of pharmaceutics. However, the antibiotic quality determination was beyond the scope of this study.…”
Section: Discussionsupporting
confidence: 80%
“…We found a higher dominance of suppliers of antibiotics from India. In the top ten suppliers of antibiotics in Tanzania, this trend has also been shown in other studies [37], indicating a good trade between Tanzania and India in the sales of pharmaceutics. However, the antibiotic quality determination was beyond the scope of this study.…”
Section: Discussionsupporting
confidence: 80%
“…Overall, the findings also indicate that the majority of antimicrobial consumption in Tanzania occurs in the private sector and that the proportion of private-sector antibiotic consumption increased annually from 2017 to 2019. This phenomenon may be explained by progressively higher volumes of private-sector pharmaceutical imports over the years, with forecasted growth of 28% by 2021 compared to the previous 5 years (Wande et al, 2019). With the exception of requirements for all national health insurance fund-approved providers to adhere to Tanzania's national standard treatment guidelines, other private-sector providers are not obliged, and therefore prescribing habits vary.…”
Section: Discussionmentioning
confidence: 99%
“…More than half of the imported medicines in Tanzania in terms of market value comes from Indian Pharmaceutical companies followed by Egypt. Antibacterial, analgesics, and antimalarial medicines were the top three categories [ 34 ]. The inability of local industries to produce enough low-cost generics medicines satisfying Good Manufacturing Practice standards [ 33 ], means imports from external sources will continue to dominate the Tanzanian market.…”
Section: Discussionmentioning
confidence: 99%
“…The inability of local industries to produce enough low-cost generics medicines satisfying Good Manufacturing Practice standards [ 33 ], means imports from external sources will continue to dominate the Tanzanian market. It is predicted that by the year 2021 the private sector market value of pharmaceuticals will increase by 28% [ 34 ]. A study by Ewen et al 2016 showed that in a sample of 24 essential medicines, prices in the private sector were 101 and 201% higher than the international reference prices for locally produced and imported medicines, respectively [ 35 ].…”
Section: Discussionmentioning
confidence: 99%